KEMAMPUAN SAMPAH KULIT KERANG DALAM MENURUNKAN KEKERUHAN AIR SUNGAI KALI LAMONG - Cicick Dwi Cahyati; Rachmaniah .; Margono . (GEMA LINGKUNGAN KESEHATAN, 2015)
TPA Benowo is a final disposal site for solid wastes generated by Surabaya community, located at KelurahanRomokalisari, Kecamatan Benowo Kota Surabaya. Every day nearly 1,200 tonnes of wastes are thrown intoTPA Benowo. This site was prepared with a land of approximately 39,7 hectares. The recent problemencountered by TPA Benowo is the leachate from the dump site that is normally discharge into Kali Lamong,now it turned out that such leachate is far above the allowable limit. Water is said to be turbid if it containslarge amount of suspended particles. Reduction of turbidity is normally done by filtering it through sandmedia. Clampshells offer an alternative for use as water filter media.This was a quasi-experimental study, using three different diameter, 1 mm, 0,5 mm, 0,3 mm. As much as 24samples were examined in this study, they were grouped into prior-to and after treatment groups, and acontrol group Sampling was performed in the morning to avoid excessive sunlight. Water was filtered throughon the same day, and followed by shipment to the laboratory right away. Data were tabulized, processedintographs, to facilitate descriptive analyses.The study found that one particular clampshell, kerang Tothok, at a diameter of 1 mm was proven to be mosteffective during treatment C, marked as 94,5% with recorded detention time of 90 minutes. Those havingdiameter of 0,5 mm is most effective during treatment C, marked at 95,8 % with recorded detention time of90 minutes. The 0,3 mm diameter is most effective at treatment C, marked at 85,7 % with recorded detentiontime of 90 minutes. The study concluded that the most effective diameter as a clampshell granules filtermedia is 0.5 mm, with reduction of 369.62 NTU or 95,8%. Further investigation is needed to learn theappropriate thickness of the clampshell granule filter.